Human Cancer Cells Sense Cytosolic Nucleic Acids Through the RIG-I–MAVS Pathway and cGAS–STING Pathway - Qiao, Yuan; Zhu, Shan; Deng, Shuanglin; Zou, Shan-Shan; Gao, Bao; Zang, Guoxia; Wu, Jing; Jiang, Yuxue; Liu, Yong-Jun; Chen, Jingtao (Frontiers in Cell and Developmental Biology, 2021)
Pattern recognition receptors (PRRs) are germline-encoded host sensors of the innate immune system. Some human cancer cells have been reported to express PRRs. However, nucleic acid sensors in human cancers have not been studied in detail. Therefore, we systematically analyzed the expression, molecular cascade, and functions of TLR3, RIG-I, MDA5, LGP2, cGAS, and STING in human cancer cells. TLR3, TRIF, RIG-I, MDA5, LGP2, and MAVS were expressed in 22 cell lines. The majority of cell lines responded to only RIG-I ligands 5ˊppp-dsRNA, Poly(I:C)-HMW, Poly(I:C)-LMW, and/or Poly(dA:dT), as revealed by IRF3 phosphorylation and IFN-β secretion. IFN-β secretion was inhibited by RIG-I and MAVS knockdown. cGAS and STING were co-expressed in 10 of 22 cell lines but IFN-β secretion was not induced by STING ligands ISD, HSV60, VACV70, Poly(dG:dC), and 3’3’-cGAMP in cGAS and STING intact cell lines. Further experiments revealed that the cGAS-STING pathway was activated, as revealed by TBK1 and IRF3 phosphorylation and IFN-β and ISG mRNA expression. These results suggest that human epithelial cancer cells respond to cytosolic RNA through the RIG-I-MAVS pathway, but only sense cytosolic DNA through the cGAS-STING pathway. These findings are relevant for cancer immunotherapy approaches based on targeting nucleic acid receptors.